The Role Of Polymorbidity During Covid-19 (Eurasian Medical Research Periodical, 2023)
We analyzed 340 cases of coronovirus infection in patients hospitalized in the COVID center, taking into account polymorbidity and its contribution to the severity and outcome of the infection. Severe polymorbidity according to CIRS was significantly more common in both men and women (P